CHEMICAL ANALYSIS AND ORGANOLEPTIC CHARACTERISTICS OF TWO MACEDONIAN VINES: WHITE TAMJANIKA AND CHARDONNAY - Manojlović, Nedeljko (ACADEMIC REVIEW, 2018)
The aim of this paper was to examine the quality of two Macedonian white wines: white incense and chardonnay and to point out the significant differences that exist between their chemical and organoleptic characteristics. This paper presents the results of the determination of analytical parameters and the organoleptic evaluation of these two Macedonian wines. Based on the results obtained, it can be concluded that wine chardonnay has a higher refractive index and lower acidity (pH) than white incense. The rn wine value moves within the allowed limits of 3-3.8. The total acid content of white incense is 5.175 g / dm3, and in chardonnay 5.025 g / dm3 expressed through tartaric acid. Since the rules stipulate the content of total acids at least 5 g / dm3 tartaric acid, it can be concluded that the obtained values meet the prescribed rules. The sugar content of white incense is 1.52 g / dm3, and the chardonnay has a slightly reduced value of 1.49 g / dm3, which is in accordance with the rulebook that prescribes that the content of sugar of dry wines can be 1-2 g / dm3 in finished product, calculated on the weight of the product. The alcohol content for white incense is 14.31 (% V / V), and for shards significantly less (9.50% V / V). On the other hand, chardonese have a significantly higher value of extract content (17.5 g / dm3) compared to 9.7 g / dm3 in white incense. The total sulfur dioxide content ranges from 30.72 for white incense to 35.84 mg / dm3 for chardones and within the limits prescribed by the rules. The results point to significant differences in the physico-chemical composition of these two wines, which also reflect their organoleptic properties. On the basis of tasting, most degustants have estimated that wine chardonnay has better oranoleptic properties.